Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1073/pnas.1710167114
|View full text |Cite
|
Sign up to set email alerts
|

WhiB6 regulation of ESX-1 gene expression is controlled by a negative feedback loop inMycobacterium marinum

Abstract: ESX (ESAT-6 system) export systems play diverse roles across mycobacterial species. Interestingly, genetic disruption of ESX systems in different species does not result in an accumulation of protein substrates in the mycobacterial cell. However, the mechanisms underlying this observation are elusive. We hypothesized that the levels of ESX substrates were regulated by a feedback-control mechanism, linking the levels of substrates to the secretory status of ESX systems. To test this hypothesis, we used a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(155 citation statements)
references
References 92 publications
10
129
1
Order By: Relevance
“…The induced genes annotated as transcriptional regulators were csoR , rv1129c , rv1460 , rv2017 , rv2250c , rv3334 , sigB , whiB3 and whiB6 (Table ). These transcription factors regulate copper homoeostasis (CsoR) (Marcus et al , ), iron–sulphur cluster biogenesis (Rv1460) (Willemse et al , ), cholesterol catabolism (Rv1129c/PrpR) (Masiewicz et al , ), the enduring hypoxic response (Rv3334) (Rustad et al , ), multiple stress responses (SigB) (Lee et al , ), redox stress and complex lipid biosynthesis (WhiB3) (Mehta and Singh, ) and virulence factor expression (WhiB6) (Bosserman et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The induced genes annotated as transcriptional regulators were csoR , rv1129c , rv1460 , rv2017 , rv2250c , rv3334 , sigB , whiB3 and whiB6 (Table ). These transcription factors regulate copper homoeostasis (CsoR) (Marcus et al , ), iron–sulphur cluster biogenesis (Rv1460) (Willemse et al , ), cholesterol catabolism (Rv1129c/PrpR) (Masiewicz et al , ), the enduring hypoxic response (Rv3334) (Rustad et al , ), multiple stress responses (SigB) (Lee et al , ), redox stress and complex lipid biosynthesis (WhiB3) (Mehta and Singh, ) and virulence factor expression (WhiB6) (Bosserman et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…NanoUHPLC-MS/MS was performed essentially as described(Bosserman et al 2017; 462 Bosserman et al 2019). 1µg of each digest was analyzed in technical triplicate and 463 biological duplicate on an Orbitrap instrument running a TOP15 data-dependent 464 acquisition (Q-Exactive Thermo San Jose, CA).…”
mentioning
confidence: 99%
“…WhiB proteins are actinobacteria-specific regulators that contain iron-sulfur clusters and are thought to act as redox-sensing transcription factors that can cause both gene activation and repression [37]. WhiB6 was suggested to be involved in the regulation of EsxA secretion [38], and subsequent studies have confirmed this suggestion [3941]. To determine whether Whib6 had an effect on the expression levels of esx-1 associated genes, we overexpressed this protein in the ESX-1-deficient M. marinum eccCb 1 transposon mutant strain.…”
Section: Resultsmentioning
confidence: 99%